Mettl1/Wdr4-Mediated m7G tRNA Methylome Is Required for Normal mRNA Translation and Embryonic Stem Cell Self-Renewal and Differentiation - Lin, Shuibin; Liu, Qi; Lelyveld, Victor S.; Choe, Junho; Szostak, Jack W.; Gregory, Richard I. (Molecular cell, 2018)
tRNAs are subject to numerous modifications, including methylation. Mutations in the human N7-methylguanosine (m7G) methyltransferase complex METTL1/WDR4 cause primordial dwarfism and brain malformation, yet the molecular and cellular function in mammals is not well understood. We developed m7G methylated tRNA immunoprecipitation sequencing (MeRIP-seq) and tRNA reduction and cleavage sequencing (TRAC-seq) to reveal the m7G tRNA methylome in mouse embryonic stem cells (mESCs). A subset of 22 tRNAs is modified at a “RAGGU” motif within the variable loop. We observe increased ribosome occupancy at the corresponding codons in Mettl1 knockout mESCs, implying widespread effects on tRNA function, ribosome pausing, and mRNA translation. Translation of cell cycle genes and those associated with brain abnormalities is particularly affected. Mettl1 or Wdr4 knockout mESCs display defective self-renewal and neural differentiation. Our study uncovers the complexity of the mammalian m7G tRNA methylome and highlights its essential role in ESCs with links to human disease. [Display omitted] •Develop MeRIP-seq and TRAC-seq for mapping of m7G modification•Reveal the m7G tRNA methylome in mammalian cells at single-nucleotide resolution•Mettl1/Wdr4-mediated m7G tRNA methylome is required for normal mRNA translation•Mettl1/Wdr4-mediated m7G tRNA methylome regulates ESC self-renewal and differentiation Lin and Liu et al. developed two independent methods, MeRIP-seq and TRAC-seq, to profile the m7G tRNA methylome in mouse ESCs and revealed that Mettl1/Wdr4-mediated m7G tRNA methylome is required for normal mRNA translation and ESC self-renewal and differentiation.